Menciptakan ABK yang Cerdas dan Berkarakter - Chatarina Novianti; Yuliani Sepe Wangge; Anselmus Mema; Siprianus See; Bonevantura R. Seto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
The aim of this community service is to help children's psychomotor development to control body movements through coordinated activities between the central nerve and muscles through games, hone children's abilities through coloring sketches, and provide reinforcement and motivation for children with special needs so that children do not inferior and able to compete in the world of education like other children. This activity was carried out at SLB Negeri Ende. The methods used in this service activity are game methods, socialization approaches and lectures. The results of the activity show that children are more enthusiastic about learning, because the material provided is material that is combined with games, so that lessons are more fun for children and not boring. The conclusion of this service is that the community service activities carried out are expected to improve the concentration and learning abilities of children with special needs at SLB. Negeri Ende